2014 International Conference on Electrical Machines (ICEM) 2014
DOI: 10.1109/icelmach.2014.6960227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unbalanced and inclined air-gap in double-stator inner-rotor axial flux permanent magnet machine

Abstract: Due to its novelty in structure, the appealing force between rotor and stator disks, axial flux (AF) permanent magnet (PM) machine are easily affected by air-gap asymmetries. In the inner-rotor double-stator AF machine, the rotor disk is assembled between two outer stators. It is usually assumed that the air-gap clearance is ideal condition in electromagnetic analysis. However, manufacturing imperfections in the machine or any perturbation to rotor disk during operation would results in an unbalanced and incli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The authors stated that the studied imperfections produce a bending torque of the stator structure and can increase the ripple torque. A similar analysis is presented in [17] for a double-stator one-rotor TCW-AFPM machine. Using quasi-3D FE simulations, it was found that the tilt of the rotor structure can increase the peak value and modify the wave-form period of cogging torque.…”
Section: Statormentioning
confidence: 77%
See 1 more Smart Citation
“…The authors stated that the studied imperfections produce a bending torque of the stator structure and can increase the ripple torque. A similar analysis is presented in [17] for a double-stator one-rotor TCW-AFPM machine. Using quasi-3D FE simulations, it was found that the tilt of the rotor structure can increase the peak value and modify the wave-form period of cogging torque.…”
Section: Statormentioning
confidence: 77%
“…In this regard, AFPM machines have been also studied, but most of the research articles focus on analyzing the effect of rotor and stator misalignments, static and dynamic eccentricity, and magnet shape selection [16][17][18][19][20][21]. The analysis of a double-rotor one-stator TCW-AFPM machine for wind power generation was presented in [16].…”
Section: Statormentioning
confidence: 99%
“…This can be extended to other cogging torque mitigating methods such as pole-slot combinations, which affect NL, p and Qs. Furthermore, nonuniformities in the airgap [30] can be analysed by analytically incorporating them in (8), in addition to other methods described in [31] and [32]. This is the simplicity of the analytical quasi 3-D technique proposed in this paper.…”
Section: Analytical Prediction Of Cogging Torquementioning
confidence: 98%
“…The flux density in the slotless air gap with eccentricity (Becc) and without eccentricity (Bno-ecc) can be estimated by modifying the air gap length in Equation (9).…”
Section: Bilinear Mappingmentioning
confidence: 99%